2000
DOI: 10.1006/viro.2000.0424
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a Subgroup A Avian Leukosis Virus [ALV(A)] Envelope Resistant to Soluble ALV(A) Surface Glycoprotein

Abstract: The host developing resistance to retroviral infection is believed to be a major force in the evolution of multiple receptor usage by retroviruses. The avian leukosis-sarcoma virus (ALV) group of retroviruses provides a powerful system for studying the envelope-receptor interactions involved in retrovirus entry; different members of this group of closely related viruses use distinct cellular receptors. Analysis of the ALV envelope subgroups suggests that the different ALVs evolved from a common ancestor by mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
45
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…An earlier study identified another region of ALV(A) hr1 (Fig. 8, residues 155 to 160) deletion of which broadened the receptor usage of the variant but allowed it to retain wild-type binding affinity for the Tva receptors (23). Despite the reports that residues in FIG.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…An earlier study identified another region of ALV(A) hr1 (Fig. 8, residues 155 to 160) deletion of which broadened the receptor usage of the variant but allowed it to retain wild-type binding affinity for the Tva receptors (23). Despite the reports that residues in FIG.…”
Section: Discussionmentioning
confidence: 96%
“…Our approach to defining these critical determinants utilizes the ability of retroviruses to escape environmental pressure by mutation and/or recombination to select a viable variant. It has been shown that even a modest level of selective pressure on ALV entry results in the generation of viral variants with altered entry properties (e.g., expanded host range or reduced receptor binding affinity) (23,24,34). These genetic approaches do not make assumptions about the location of interaction determinants in SU (in contrast to sitedirected mutagenesis), and viral variants with multiple mutations can be selected to identify functional but noncontiguous determinants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This sequence divergence may dictate subtle differences in this region and determine specificity in receptor usage. Indeed, it was reported that several ASLV-A variants which were genetically selected for a soluble form of quail Tva could not use quail Tva but could still efficiently use chicken Tva as the receptor in viral entry (14)(15)(16). These results seem to suggest that specific residues in the N terminus of Tva play an important role in specificity in receptor usage.…”
Section: Discussionmentioning
confidence: 99%